The Human Amnion Epithelial Cell Secretome Decreases Hepatic Fibrosis in Mice with Chronic Liver Fibrosis - Alhomrani, Majid; Correia, Jeanne; Zavou, Marcus; Leaw, Bryan; Kuk, Nathan; Xu, Rong; Saad, Mohamed I.; Hodge, Alexander; Greening, David W.; Lim, Rebecca; Sievert, William (Frontiers in Pharmacology, 2017)
Background: Hepatic stellate cells (HSCs) are the primary collagen-secreting cells in the liver. While HSCs are the major cell type involved in the pathogenesis of liver fibrosis, hepatic macrophages also play an important role in mediating fibrogenesis and fibrosis resolution. Previously, we observed a reduction in HSC activation, proliferation and collagen synthesis following exposure to human amnion epithelial cells (hAEC) and hAEC-conditioned media (hAEC-CM). This suggested that specific factors secreted by hAECs might be effective in ameliorating liver fibrosis. hAEC-derived extracellular vesicles (hAEC-EVs), which are nanosized (40-100nm) membrane bound vesicles, may act as novel cell-cell communicators. Accordingly, we evaluated the efficacy of hAEC-EV in modulating liver fibrosis in a mouse model of chronic liver fibrosis and in human HSC. Methods: hAEC-EVs were isolated and characterised. C57BL/6 mice with CCl4 induced liver fibrosis were administered hAEC-EV, hAEC-CM or hAEC-EV depleted medium (hAEC EVDM). LX-2 cells, a human HSC line, and bone marrow derived mouse macrophages were exposed to hAEC-EV, hAEC-CM and hAEC-EVDM. Mass spectrometry was used to examine the proteome profile of each preparation. Results: The extent of liver fibrosis and number of activated HSCs were reduced significantly in CCl4 treated mice given hAEC-EVs, hAEC-CM and hAEC EVDM compared to untreated controls. Hepatic macrophages were significantly decreased in all treatment groups, where a predominant M2 phenotype was observed. Human HSCs cultured with hAEC-EV and hAEC-CM displayed a significant reduction in collagen synthesis and hAEC-EV, hAEC-CM and hAEC EVDM altered macrophage polarization in bone marrow-derived mouse macrophages. Proteome analysis showed that 163 and 164 proteins were unique to hAEC-CM and hAEC-EVDM, respectively, and 67 proteins were co-identified components with the hAEC-EV fraction. Conclusion: This study provides novel data showing that hAEC-derived EVs significantly reduced liver fibrosis and macrophage infiltration to an extent similar to hAEC-EVDM and hAEC-CM. hAEC-EV based therapy may be a potential therapeutic option for liver fibrosis.